Changing environments and biomolecule coronas: consequences and challenges for the design of environmentally acceptable engineered nanoparticles. Issue 18 (11th July 2018) - Markiewicz, Marta; Kumirska, Jolanta; Lynch, Iseult; Matzke, Marianne; Köser, Jan; Bemowsky, Steve; Docter, Dominic; Stauber, Roland; Westmeier, Dana; Stolte, Stefan
Abstract : Components of natural waters (salts, NOM) mitigate negative impacts of nanomaterials via surface passivation and stabilisation against dissolution. Abstract : Nanomaterials (NMs) are gaining increasing commercial importance due to a variety of properties that cannot be achieved with bulk materials. Yet the assessment of their environmental impacts lags behind the technological development. First attempts towards designing inherently safer NMs have been made, yet we are still unable to formulate rules of green nano-design, especially in terms of mitigating (long-term) toxicity and bioaccumulation. Importantly, NMs released to the environment acquire a so called 'environmental corona' – a complex layer of spontaneously adsorbed biomolecules – that significantly impacts their behaviour and fate. This review integrates the current literature on the impact of environmental conditions on NMs fate and behaviour, including corona formation, colloidal stability, reactivity, and toxicty, using a broad range of environmentally relevant NMs. Collectively, components of natural waters (such as salts and/or natural organic matter) often mitigate negative impacts of NMs via different mechanisms including surface passivation and stabilisation against dissolution. The review concludes by discussing some initial strategies on how to rationally design more environmentally acceptable NMs.